Low Serum Anti Mullerian Hormone as a Risk Factor for Cardiovascular Disease in Child-Bearing Age Women - Ratnani, Daniela; Pramudianti, M.I. Diah (Rumah Sakit Umum Daerah Dr. Moewardi, 2025)
IntroductionCardiovascular disease (CVD) is the leading cause of global death. Incidence of having CVD is influenced by general risk factors and gender-related risk (preeclampsia, miscarriage, premature birth, contraception and hormonal therapy). Women of childbearing age have lower risk of CVD than men. Anti Mullerian Hormone (AMH) can be used to predict CVD. This study aimed to know association between Serum AMH level with CVD. MethodsThis study was an observational analytic, cross-sectional study. Subjects study is women with childbearing age (18-44 years old) who doing laboratory examination from May until November 2024. The exclusion criteria were patients who under chemoradiation therapy, pregnancy and have history of fertility disorder such as polycystic ovarian syndrome (PCOS). Data was subjected to bivariate testung chi square and multivariate regression logistic with Statistical Package for the Sociak Sciences (SPSS) version 29.0. ResultsA total of 57 subjects were being analyzed. Bivariate analysis showed that Serum AMH (p<0,001) have correlation with CVD. Multivariate analysis shows that Serum AMH <0,69 ng/mL (p<0,001; RR=34,049) were independently associated with CVD. ConclusionsSerum AMH <0,69 ng/mL (PR:34,05; 95% CI: 6,245–185,630, p=<0,001) increased risk of having CVD in women with childbearing age.